Naphthoquinone derivatives as P-glycoprotein inducers in inflammatory bowel disease: 2D monolayers, 3D spheroids, and in vivo models. (May 2022) - Mahmoud, Nuha; Hegazy, Mohamed-Elamir F.; Wadie, Walaa; Elbadawi, Mohamed; Fleischer, Edmond; Klinger, Anette; Bringmann, Gerhard; Khayyal, Mohamed T.; Efferth, Thomas
Abstract: Inflammatory bowel disease (IBD) represents a chronic inflammation of the gastrointestinal tract characterized by an overreaction of immune responses and damage at the intestinal mucosal barrier. P-glycoprotein (P-gp) plays a key role to protect the intestinal barrier from xenobiotic accumulation and suppressing excessive immune responses. Therefore, induction/activation of P-gp function could serve as a novel therapeutic target to treat IBD. This study aimed to evaluate the potential therapeutic values of naphthoquinone derivatives (NQ-1 - NQ-8 ) as P-gp modulators to counterbalance intestinal inflammation. The data indicate that NQ-2, NQ-3, and NQ-4 act as P-gp inducers/activators and are recognized as substrates for P-gp. The three derivatives possess anti-inflammatory effects mediated by suppression of NF-κB and HDAC6 activity in Caco2 monolayer cells. Besides, they reversed LPS-induced intestinal barrier dysfunction by enhancing the expression of P-gp and ZO-1 tight junction proteins in a Caco-2 spheroid model. NQ-2, NQ-3, and NQ-4 showed a robust inhibitory effect on IL-1β maturation in LPS-primed THP-1 cells. This effect may contribute to alleviate the inflammatory cascades associated with IBD. Distinctively, NQ-2 and NQ-3 exerted anti-NLRP3 inflammasome activity evidenced by the inhibition of CASP-1 activity and the promotion of autophagy. Both compounds induced disruptions of the microtubule network in transfected U2OS-GFP-α-tubulin cells. Treatment with NQ-2 remarkably attenuated dextran sulfate sodium (DSS)-induced colitis in rats by suppressing changes in colon length, colon mass index, and intestinal histopathology scores. Thus, 1, 4-naphthoquinone derivatives such as NQ-2 may provide potential therapeutic anti-inflammatory effects for IBD patients and for other NLRP3-associated inflammatory diseases. Graphical Abstract: ga1